Business Model for Brazilian Indie Game Studios in Game Software Ecosystems - Xavier, Bruno; Viana, Davi; Santos, Rodrigo Pereira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Context: The Software Ecosystem (SECO) strategy dominates the digital game industry. The leading game companies adopted SECO dynamics, forcing external actors (e.g., game studios) to adapt to a highly competitive scenario. Objective: Considering the significant growth of the Brazilian digital games industry in the last years, this study aims to present and evaluate a business model proposed for the independent Brazilian game studios immersed in the Game SECO (GSECO) context. Method:We explained the proposed model and reported on 15 online interviews to capture comments and suggestions. Three researchers applied the Grounded Theory (GT) procedures to extract actions to improve the business model. Results: 25 suggestions to improve the proposed business model emerged. Finally, we use the business model concepts and subdomains to both define the suggestions to be adopted and identify opportunities for future work. Conclusion: The first version of the business model for independent studios in GSECO reached a high level of relevance in its first evaluation. Some interviewees highlighted the differential of the model in directing the construction of a digital game business contextualized in the Brazilian scenario and how the tool can directly contribute to the maturity of the industry. As future work, we identified the need to expand the model for all subdomains and new evaluation with actors from different regions